Effect of Cooking and in vitro Digestion on the Polyphenols and Antioxidant Properties of Asparagus officinalis L. cultivars - Angela Di Matteo; Antonio Paolillo; Lidia Ciriaco; Juliane Lima da Silva; Stefania De Pascale; Luana Izzo (Foods)
Asparagus (Asparagus officinalis L.) is widely recognized for its nutritional and functional properties, attributed to its rich content of polyphenols and antioxidant compounds. However, the content of compounds that remains bioaccessible following typical domestic preparation and digestion remains unclear. This study assessed the polyphenolic profile and antioxidant capacity of the edible portion of two A. officinalis cultivars (Placoseps and Darlise), harvested in different seasons, in edible form, cooked (using boiling on an induction cooktop), and cooked-digested extracts. Rutin emerged as the most abundant in all analyzed samples; its concentration in the edible part reached 1770.72 in Placoseps and 995.20 mg/kg in Darlise. Cooking increased rutin content in April-harvested asparagus to 1966.00 in Placoseps and 2042.44 mg/kg in Darlise, reflecting an increase of more than 2.5-fold compared to the respective values observed at the earlier harvest. Despite the substantial reduction in bioactive compounds observed during in vitro gastrointestinal digestion, a total of 146.95 to 454.58 mg/kg of bioaccessible compounds remaining available for potential intestinal absorption after digestion across both cultivars and harvest periods. These results provide a greater understanding of the behavior of polyphenol-rich vegetables and underscore the importance of simulating gastrointestinal processes when assessing the health-promoting potential of bioactive compounds.